HUBUNGAN TIPE KEPRIBADIAN DENGAN STRES FINANSIAL DI KALANGAN KARYAWAN - Sarah Enzelika; Putri, Sary; Gunawan, Richard; Prameswari, Annisa (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study examines the relationship between the Big Five personality dimensions and the level of stress caused caused by financial problem among employees. Financial stress refers to difficulties in meeting basic needs, leading to emotional strain, while the personality traits include Neuroticism, Extraversion, Openness, Agreeableness, and Conscientiousness. A quantitative cross-sectional method was used, involving a minimum of 100 active employees aged 20–56, selected through purposive sampling based on Slovin’s formula (? = 0.10). Personality traits were measured using the NEO-PI-R, and financial stress was assessed using the Financial Stress Scale developed by Heo et al. (2020). Pearson correlation and multiple linear regression analyses revealed that Neuroticism had the strongest association with financial stress (r = 0.645; p < 0.05), followed by Conscientiousness (r = 0.583), Openness (r = 0.417), Agreeableness (r = 0.340), and Extraversion (r = 0.211). This Study indicates that the higher the tendency toward neuroticism, the greater the perceived financial stress, while the higher the aspect of extraversion in an individual, the lower the perceived impact of financial stress. Keyword : Big Five Personality, Financial Stress, Employee